The Performance of the Textiles and Apparel Sector and the Challenge of Environmental Sustainability in Ghana: A Qualitative Study - Zanu, Joana Akweley (Journal of Education and Practice, 2023)
Purpose: The study assessed empirically how production and consumer behaviour can instigate the reduction of carbon footprint in the textiles and apparel industry to promote sustainable development. Methodology: The study was predominantly qualitative with a sample size of 15 textiles and apparel manufacturers managers/owners were selected purposively from three regions of Ghana. Findings: The results suggest that respondents hardly employ any strategy to facilitate environmental sustainability. Even though they are aware of the concept of carbon footprint, they lack the basic techniques to assess their environmental performance in terms of sustainability. Unique Contribution to Theory, Policy and Practice: The study can significantly contribute to policy and practice in Ghana and elsewhere by shaping regulatory frameworks, encouraging sustainable business practices, enhancing education and training, guiding EIAs, and fostering consumer awareness.